Analysis of Student Satisfaction with Facilities and guidelines for Physical Education Learning at SDN 1 Krandegan - Edi Mulyono; Eko Sudarmanto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
In addition to teachers, infrastructure for learning support must be taken into account in order to achieve the idea of effective learning. The sample in this study consisted of 49 SDN 1 Krandegan students, and the sampling method used systematic random sampling. While conducting this form of descriptive study, which is strengthened by quantitative research, data is collected through observation, questionnaires, and interviews. The conclusion is that the level of student satisfaction with the facilities and infrastructure in physical education lessons at SDN 1 Krandegan is in the "Very High" category, which is represented by 8.16% of the students, "High" by 45% of the students, "Enough" by 18% of the students, "Low" by 22.45% of the students, and "Very Low" by 6.12% of the students (3 students). Krandegan falls in the "High" category for student satisfaction with the infrastructure and facilities used in physical education courses at SDN 1 Krandegan.